The promotion of critical reading through the digital environment: A study on the virtual epitexts used to promote children’s picturebooks - Tabernero-Sala, Rosa; Colón-Castillo, María Jesús (Frontiers in Psychology, 2023)
The most recent research studies in the field of reading describe a new cultural ecosystem in which analog and digital reading coexist and contribute to transform what is read, either through the way reading is performed or by promoting reading. In this context, the training of critical readers is particularly important, an aspect emphasized by UNESCO and the curriculum frameworks based on its premises. In order to provide data for reflection on this question, this paper presents an essentially qualitative and interpretive documentary study of a sample of 836 virtual epitexts that promote children’s picturebooks. The selected documents consist of the postings by 45 publishing houses between 2020 and 2022 on their YouTube and Vimeo channels. The results of the content analysis present the current tendencies in digital promotion of children’s books and the strategies most likely to encourage critical reading. The insistence on the author’s presence, the emphasis on the materiality of the book as an object, the strengthening of artistic discourse and the hybridization of reality and fiction, among other aspects, all propose a type of reading that favors the development of critical thinking. The results are complemented by a selection of virtual epitexts suggested to mediators and readers as resources of interest in promoting critical reading in socio-educational contexts.